The Role of Emotions in The Formation of Social Relationships in Primary School-Age Children: A Psychological and Educational Approach - Ertanti, Devi wahyu; Hanurawan, Fattah; Suciptaningsih, Oktaviani Adhi (MODELING: Jurnal Program Studi PGMI, 2024)
The present study aims to examine the influence of emotions on the formation of social interactions among primary school-aged children in Malang City. The research sample consisted of two hundred children selected randomly from ten public or private elementary schools. The frequency and intensity of children's emotional expressions and emotional management abilities were primarily assessed through questionnaires and observation guides. Diverse aspects of social interactions and emotions were evaluated using a Likert scale ranging from "very rarely" to "very often" on a scale of 1 to 5. Multiple linear regression was utilized to examine the relationship between emotional regulation and relationship quality, and the Pearson Product Moment Correlation Algorithm was implemented to assess the validity of the instruments. Significant positive correlations were observed between the number of peers one has and the degree of happiness expressed. However, no observable correlation was found between the number of acquaintances or social interactions and emotions of sadness or rage.